2014
DOI: 10.1002/zaac.201400539
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Brasses with Spontaneous Magnetization: Atom Site Preferences and Magnetism in the Fe‐Zn and Fe‐Pd‐Zn Phase Spaces

Abstract: Abstract. The γ-brasses in the binary Fe-Zn system were re-examined as part of the discovery of a new series of Fe-Pd-Zn γ-brass compounds in the Zn-rich region of the Fe-Pd-Zn phase space. Fe 2+x Zn 11-x , x = 1.60(4)-1.99(9), and Fe x Pd 2.2-y Zn 10.8-x+y , x = 0.08(5)-2.46(8); y = 0.00(1)-1.44(4), all crystallize in the cubic crystal system, space group I43m, with corresponding ranges of the lattice parameter of 8.977(1)-8.979(1) Å and 9.1028(4)-9.0347(2) Å as x increases, as determined by single-crystal X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Based on the OD ment made in the past by four research groups in the Fe and Zn occupancy behaviors especially for the central site of these (Zn,Fe) 12 icosahedra. While exclusive occupancy by Zn atoms was claimed by Johansson et al, 28) exclusive occupancy by Fe atoms was claimed by Brandon et al, 29) Belin et al, 33) and Xie et al 50) Our results of crystal structure refinement of the Γ phase compounds with some different chemical compositions by synchrotron X-ray diffraction have indicated that the central site of (Zn,Fe) 12 icosahedra is occupied exclusively by an Fe atom regardless of chemical compositions (Fig. 9).…”
Section: δ 1p Phase (Fe 13 Zn 126 )supporting
confidence: 48%
“…Based on the OD ment made in the past by four research groups in the Fe and Zn occupancy behaviors especially for the central site of these (Zn,Fe) 12 icosahedra. While exclusive occupancy by Zn atoms was claimed by Johansson et al, 28) exclusive occupancy by Fe atoms was claimed by Brandon et al, 29) Belin et al, 33) and Xie et al 50) Our results of crystal structure refinement of the Γ phase compounds with some different chemical compositions by synchrotron X-ray diffraction have indicated that the central site of (Zn,Fe) 12 icosahedra is occupied exclusively by an Fe atom regardless of chemical compositions (Fig. 9).…”
Section: δ 1p Phase (Fe 13 Zn 126 )supporting
confidence: 48%
“…Because the ¡-Fe(Zn) phase has a body-centered cubic structure and contains more than 50 at% of Fe, it is assumed to be soft magnetic, while the !-FeZn phase is nonmagnetic at room temperature. 32) Moreover, in Fig. 10(c), a ring-like pattern is observed (indicated by the red arrow), which suggests presence of an amorphous or fine nanocrystalline phase in addition to ¡-Fe(Zn) in the Zn-diffused phase.…”
Section: Resultsmentioning
confidence: 92%
“…Because the ¥-FeZn phase was non-magnetic, 44) the soft magnetic ¡-FeZn phase was thought to be magnetically isolated from hard magnetic Sm 2 Fe 17 N 3 phase resulting in high coercivity even though there was a knick in hysteresis loop. 24,25)…”
Section: Phase and Microstructural Changesmentioning
confidence: 99%